B) m(x) = -4 (x + 3) -2
C) t(x) = -8x^2 (x^2 - 6) + 1
D) h(x) = 3x (x - 2) - 4
Answer:
D
Step-by-step explanation:
3x (x-2) - 4
3x²-6x-4
I hope it's helpful
=============================================
Work Shown:
f(x) - g(x) = ( f(x) ) - ( g(x) )
f(x) - g(x) = ( -x+5 ) - ( 3x+2 )
f(x) - g(x) = -x+5 - 3x - 2
f(x) - g(x) = (-x-3x) + (5-2)
f(x) - g(x) = -4x+3
In step 3, make sure to distribute the negative to everything in the parenthesis for (3x+2)
Answer:
720
Step-by-step explanation:
Answer:
110
Step-by-step explanation: